Mapping the Distribution and Dispersal Profile of Plumeria pudica as an Ornamental Plant in Siquijor Island - Gozon, Patrick Andrew E. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2025)
Siquijor is a small isolated island, accessible by about an hour boat ride from the nearest port of Dumaguete. But even with the isolation, a great part of its coastal areas is becoming highly densed with residential houses. Along with this urbanization, exotic plants are becoming noticeable in backyard gardens especially along the island’s circumferential coastal road. Plumeria pudica was introduced to the Philippines in the 1980’s but it was only in the 2000’s that it became popular as a garden plant in the Philippines. It is common as an ornamental plant in Metro Manila, but in recent years this Plumeria was becoming more noticeably present in household gardens and public landscapes in certain provinces. In the period from 2015 to 2019, a span of five years, the P. pudica became a common sight in household and resort gardens flanking the major roadways in Siquijor Island. The research would attempt to map the origins and the distribution profile of the plant in the island by determining P. pudica’s occurrence in the different towns. The study would also try to determine the distribution method by tracing back the source of major landscapes with pertinent presence of the plant.